Effects of light-emitting Diode therapy on recovery of adult male Futsal players - De Freitas, Victor Hugo (2021)
The aim of this study was to investigate the effects of light-emitting diode (LED) therapy on markers of physical performance, muscle damage, inflammation, and oxidative stress up to 24h post the Futsal-Specific Intermittent Shuttle Protocol (FISP). Ten adult futsal players performed the FISP seven days apart. Participants were randomized into two groups that received LED (630 nm; 300 mW; 4.6 J/cm2, 6 J per point, 120 J on each thigh) or Placebo. Heart rate (HR) and blood lactate concentration [Lac] were collected during the FISPs. Blood samples were collected for analysis of creatine kinase (CK), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and advanced oxidation protein products (AOPP), and countermovement jump (CMJ) and perceived muscle soreness were assessed pre, post, and 24h post FISP. LED and Placebo groups presented similar mean HR (p = .58) and [Lac] (p = .86) during the FISPs. Interaction (p < .01) and time effects (p < .01) were observed for CK, with both Placebo (p < .01) and LED (p < .01) increasing CK at the post moment compared to pre. A time effect was found for CMJ (p < .01) and IL-6 (p < .01), showing that CMJ presented lower values at post (p < .01) and 24h post (p = .01) compared to the pre moment, and IL-6 increased at post compared to pre (p < .01) and returned to pre values 24h post FISP. Interaction, time, and group effects were not reported for muscle soreness, TNF-α, or AOPP (p > .05). In conclusion, LED therapy altered CK behavior post FISP, but did not change markers of physical performance, muscle soreness, inflammation, or oxidative stress of futsal players up to 24h post FISP.